Internal human based threats and security controls in computerized banking systems: evidence from Malaysia - Zainol, Zaini; Puat Nelson, Sherliza; Malami, Abu Bakar (2012)
Malaysia being a unique capital market, practices dual banking system to capture the disaggregation of conventional and Islamic banking systems. However, like most financial institutions, no bank is isolated from security threats, even if, it comes from within the organization. Thus the objective of this study is to examine bank managers’ experience on human based security threats and the existence of human based security controls in computerized banking systems (CBS) in Malaysia. Since most major financial institutions operate in the capital city of Kuala Lumpur, questionnaires were sent to some of these bank branches in Kuala Lumpur. Findings revealed that managers recognized the personal policies recruitment procedure, segregation of duties and physical access control as ways to mitigate risks of human security threats. Hence, provide insights of how internal control system of a financial institution can be improved as a means to reduce security threats that have monetary implications. Finally, the study provides a platform for promoting an efficient and effective internal control practices among financial institutions in Malaysia.